Collision-free process technology for arrayed multipoint devices in coffee machines - YU, Jiao; LI, Chenghai; CHEN, Chaoxue; SHAO, Lifeng; XU, Bifeng (Food Science and Technology, 2023)
Coffee machines have become very popular in recent years, but their lack of functionality still requires a great deal of manual maintenance, which inevitably has many hidden dangers. Coffee machines with radio frequency identification systems (RFID) are more effective in reducing losses due to manual labor, and increasing efficiency. However, collision problems in RFID systems can seriously affect the performance of the system. In this paper, we propose a specific solution to such problems by proposing a collision-free process technology for arrayed multipoint devices. And this technique is successfully applied in a coffee machine. Through design experiments, after 10,000 repeated tests, no collision error occurred. The problem of collisions in coffee machines with RFID mechanisms has been successfully solved.